Anatomical variations of the lung fissures assessed by High Resolution Computed Tomography (HRCT) of chest – a cross-sectional study at tertiary center of Nepal - KC, Sudeep; Gyawali, Sushila (Journal of Patan Academy of Health Sciences, 2024)
Introduction: The lungs are a pair of vital organs of respiration which are divided into lobes by fissures which facilitate the movements and uniform expansion of lobes. The fissure may be complete, incomplete, or absent; knowledge of which is vital for both clinician and surgeons. High Resolution Computed tomography (HRCT) chest can clearly depict the fissural anatomical variation. The objective of this study was to analyze the morphology of lung fissures undergoing HRCT.Method: This cross-sectional study was done among 247 patients undergoing HRCT in Dept. of Radiology, Patan Hospital. The HRCT images were visually analyzed and categorized. Statistical analysis was performed using SPSS.Result: Out of 247 patients, classical trilobed right and bilobed left lung was seen in only 69(24.94%) subjects. Rest of the subjects had some anatomical variation of lung fissure. Incomplete oblique fissure was seen in 23(9.31%) and 18(7.28%) on the right and left side respectively. The inferior accessory fissure was seen among 50(20.24%) individuals, followed by left minor fissure among 23(9.31%), superior accessory fissure among 17(6.88%), fissure in right middle lobe among 23(9.31%) and azygyous fissure among six (2.41%). The significant difference was only seen in the completeness oblique fissure with respect to gender (p